Effect of processing and substitution levels of Ukwa (Treculia africana) on the anti-nutrient factors, in-vitro starch and protein digestibility and total essential amino-acid content of snack bars - Edima-Nyah, Anne P.; Ntukidem, Victor E.; Ekanem, Moses C.; Ojimelukwe, Philippa C.; Nwabueze, Titus U. (Frontiers in Sustainable Food Systems, 2023)
Ukwa, an indigenous edible seed, was processed into whole, dehulled, malted and defatted flours. Anti-nutrient content and proximate compositions of the flours were determined. Processing significantly reduced the anti-nutrient content and increased protein content. Up to 51.72% reduction of tannin was obtained by dehulling. Defatting, malting and dehulling resulted in 18.75, 34.37 and 65.62% reduction respectively in oxalate content. Highest reduction was obtained by dehulling, and was 70.69% in phytate, 79.95% in saponin, and 48.17% in trypsin inhibitor activity. Maize and coconut flours were blended with the respective Ukwa flours at the ratio of 0:5:5, 20:75:5, 25:70:5, 30:65:5, 35:60:5 and 5:0:5 for Ukwa flour:Maize flour:Coconut grits respectively for development of snack bars. A two-factor factorial experiment in a completely randomized block design was applied for the study of the effect of processing, substituted levels of Ukwa flour and the interaction of the two variables on the responses analyzed. Crude protein content of snack bars had 16.16 to 2.46 % substitution main effect, and 1.43 to 22.65 % processing main effect. In-vitro protein and starch digestibility increased with processing and decreased with increase in substituted level of Ukwa in the blend. Improvement, up to 9.97% by dehulling, 9.86% by malting and 8.64% by defatting, was recorded in in-vitro protein digestibility. An increase of 3.00 to 24.10% by defatting, 5.90 to 29.09% by malting and 9.70 to 31 80% by dehulling was recorded in in-vitro starch digestibility. Snack bars formulated with 20% Ukwa showed the highest in-vitro starch and protein digestibility irrespective of the method of processing. Malted Ukwa based snack bars recorded the highest values of total essential amino-acids. Processing of this nutritious seeds and use of its flour to develop snack bars could enhance utilization and give convenience to consumers and encourage extensive farming of the crop.